Development of the EAEU regional trade through the formation of some institutional and economic factors of integration - Skirko, Natallia I. (Journal of the Belarusian State University. International Relations, 2020)
The article analyses the inconsistency of the current state of the EAEU mutual trade. On the one hand, it is characterised by low quantitative indicators and objective difficulties in increasing volumes. On the other, the current practice of increasing foreign trade by countries shows not only how to use features in a single space but also about opportunities for the protection of national entities at their national segments of the union market. Creation of the new factors of competitiveness at the present stage of integration of the EAEU requires a common approach to the formation of common markets, the use of single technical regulations of the Eurasian Economic Union, and additional growth in the mobility of existing factors of production, that has a significant impact on the increased trade in comparison with the further reduction of customs tariffs, and an additional increase in the mobility of existing factors of production.
Keywords: economic integration; regional trade; trade with third countries; Eurasian integration; free movement of goods, services, capital, labour; obstacles to trade; restrictions on free trade; exceptions to the general rules of trade; barriers to mutual access to the domestic market